Cyber Dating Abuse Victimization: Links With Psychosocial Functioning - Duerksen, Kari N. (Journal of interpersonal violence, 2021)
It is well established that technology can be used to enact intimate partner violence (IPV). However, less is known about how cyber dating abuse (CDA) is associated with psychosocial functioning, especially when accounting for other forms of frequently co-occurring IPV victimization. The current study sought to determine the unique associations of CDA victimization when controlling for multiple forms of in-person IPV victimization. Two hundred seventy-eight men and women between 17 and 25 years of age (M = 20.5, SD = 1.9) who were currently in an intimate relationship for at least 3 months participated in this study. Participants completed questionnaires about their IPV and CDA victimization, as well as a range of indices of psychosocial well-being. Experiencing CDA victimization was related to increased alcohol use for both men and women, and increased fear of partner for women, even after controlling for in-person IPV. For depression, perceived stress, relationship satisfaction, quality of life, social support, and post-traumatic stress, CDA victimization did not predict levels above in-person IPV victimization. Although these results suggest some unique associations between CDA victimization and aspects of psychosocial well-being that require further attention, they also highlight that CDA often occurs within a broader pattern of abuse that includes in-person IPV. These results suggest that the need for prevention and treatment for relationships that involve in-person abuse is still most salient, and that a narrow focus on CDA may limit the utility of prevention and treatment efforts. Further work is needed to integrate research on in-person and CDA victimization, rather than to create a new field of research and practice based solely on CDA.